Symptom analysis of Parkinson disease using SVM-SMO and Ada-Boost classifiers - Billah, Muhtasim (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.